(untitled) (Mustansiria Dental Journal, 2023)
Background: Since the 1980s, as the cost of noble metals has increased, more base metal alloys have been used in fixed and removable prostheses. Cobalt-chromium (Co-Cr) alloys are one of the most widely used base metal alloys in the prosthetic dental department and have several clinical uses. Co-Cr alloys are frequently used as having excellent biocompatibility, great strength, good resistance to tarnish, corrosion, and wear, as well as being heat-resistant and non-magnetic. Materials and Methods: For the ion release test, seventy specimens of a cobalt-chrome alloy disc with dimensions of 5 mm in diameter and 3 mm in thickness were created. They were divided into five groups, each of which had 14 specimens, based on the manufacturing method as follows: new cast alloy group; selective laser melting group (3D printer specimens); once recast alloy + old selective laser melting group; new cast + once recast alloy group; once recast alloy group. Result: The outcomes showed that there were no statistically significant differences in ion release in any of the groups examined (P>0.05). Conclusion: The production technique and alloy composition have a slight influence on ion release. A positive clinical response is anticipated, since it was found that every group met the ionic release criteria of the international standards.